Enhanced understanding of cinnamaldehyde’s therapeutic potential in osteoarthritis through bioinformatics and mechanistic validation of its anti-apoptotic effect - Sheng, Yueyang; Zhai, Ruiqing; Li, Shan; Wang, Xinyu; Wang, Ying; Cui, Zhengguo; Wang, Chao; Wang, Qianqian; Zhang, Yanzhuo; Wu, Chengai (Frontiers in Medicine, 2024)
Osteoarthritis (OA) represents a globally prevalent joint disorder, affecting an estimated 240 million individuals worldwide. Cinnamaldehyde, recognized for its extensive anti-inflammatory and anti-aging pharmacological properties across various cell types, has yet to be evaluated for its potential effects on apoptosis in OA chondrocytes. This study aimed to assess the effectiveness of cinnamaldehyde in alleviating knee osteoarthritis by reducing chondrocyte apoptosis. Initially, bioinformatics analysis was employed to identify apoptosis-associated differentially expressed genes (APDEGs). These findings led to an examination of gene expression datasets GSE55235 and GSE114007 utilizing weighted gene co-expression network analysis (WGCNA). The gene modules highlighted were subsequently cross-referenced with APDEGs to pinpoint those specific to OA. LASSO regression analysis was then applied to construct a risk model, which, coupled with datasets GSE114007, GSE55457, and GSE12021, supported ROC validation. Cellular experiments and blood analyses from OA patients revealed that cinnamaldehyde administration could remediate the abnormal expression of pivotal apoptosis-related genes in these subjects. Our results suggested that cinnamaldehyde may influence knee osteoarthritis through its regulatory impact on specific apoptosis-related genes, namely ZFAND5, BCL6, ELL2, FOSL2, MARCKS, and SGCD. These insights provide substantial theoretical backing for the clinical application of cinnamaldehyde in OA treatment. Additionally, the identification of three novel apoptotic targets in OA chondrocytes-ZFAND5, ELL2, and SGCD-highlights potential therapeutic avenues for future OA interventions.